The Diversity of Aquatic Flora in Twin Lake and Talang Lake, Solok, West Sumatra - Christy, Panji; Syamsuardi, Syamsuardi; Nurainas, Nurainas (Jurnal Biologi Tropis, 2025)
West Sumatra has five lakes renowned as natural resource with unique landscapes that are also utilized for various antrophogenic purposes. Among them, in Solok regency there are three lakes that are famous as tourist destinations and the main resource of livelihood for the local community, namely the Twin Lakes (Lake Diatas and Dibawah), also the smaller one is Talang Lake. This study aim to analyze the diversity of aquatic flora in Lake Diatas, Dibawah and Talang. Field surveys was conducted to inventory the aquatic flora that lives in and edge of the lakes. Based on initial surveys that was carried out, total 25 species, 25 genus, 18 family aquatic flora found in three lakes in Solok Regency. Poaceae and Cyperaceae is common family that usually apper in edge of the lakes. One species, Potamogeton sumatranus, is an endemic aquatic flora of Sumatra. And one type was found, namely Ceratophyllum demersum, which is thought to be a New Record species in Lake Diatas, West Sumatra.